Research of innovative activity of enterprises of the Republic of Kazakhstan - Кирдасинова, К.; Сейдалиева, Д.; Саргаева, Н. (Journal of Economic Research & Business Administration, 2017)
The effectiveness of the economic policy of the state is the main aspect to the successful development of the country in general and its component is industrial and innovation policy. New industrialization of the country at a historic juncture of its formation suggests a new economic system, susceptible to upgrading, restructuring, innovation, creation and introduction of new products and technologies, increasing the competitiveness of production, these aspects led to the research by the authors. Industrial-innovative policy of the state and the mechanisms of its implementation were considered in this article. This article deals with the problems of development of business in the Republic of Kazakhstan. Characteristics and natural conditions functioning of small and medium-sized enterprises were analyzed in the country and regional level. The article reveals and substantiates the necessity of state support of entrepreneurship. Economic evaluation of enterprises activity in Kazakhstan was conducted in the field of innovation. The problems, preventing active innovative development of Kazakhstan enterprises were shown in the article as well. According to the research, the authors proved the main directions of solving problems of innovation activity improvement in Kazakhstan.